Advanced Microsystems for Automotive Applications 2008 - Valldorf, Jürgen (Springer, 2017)
Market -- Advanced Safety Systems -- The Opportunity for Semiconductor Vendors -- Safety -- Dual Frequency Methods for Identifying Hidden Targets in Road Traffic -- Multi Spectral Pedestrian Detection and Localization -- Car Driver Monitoring by Networking Vital Data -- MDSI Range Camera Calibration -- Laserscanner Based Cooperative Pre-Data-Fusion -- Satellite-Based System for Predictive Control in Vehicles and its Field of Applications -- Results of the EC-Project INTERSAFE -- Powertrain -- Crank Angle Resolved Determination of Fuel-Concentration and Air/Fuel Ratio in a SI-Production Engine by Using a Modified Optical Spark Plug -- Two-Line LIF-Emission Thermometry for Gas-Temperature Determination in IC-Engines -- Comfort and HMI -- Human Vehicle Interaction Based On Electric Field Sensing -- Networked Vehicle -- Automotive 1 Gbit/s Link Goes Standard -- Components and Generic Sensor Technologies -- Imaging Millimeter Wave Radar with Phased Array Antenna -- Tungsten-Titanium as Advanced Material for RF-MEMS Switches -- Local Modification of Fired LTCC Substrates for High Frequency Applications -- Determination of Complex Permittivity of LRR Radome Materials Using a Scalar Quasi-Optical Measurement System -- Speed Sensors for Automotive Applications Based on Integrated GMR Technology -- Micro-Rotation Angle Sensor with Integrated Hall IC -- Scaled Test Bed for Automotive Experiments: Evaluation of Single Accelerometer Electronic Stability Control -- A New Micromechanical Pressure Sensor for Automotive Airbag Applications -- Trusting Your Senses.